Electrostatic Interaction Tailored Anion-Rich Solvation Sheath Stabilizing High-Voltage Lithium Metal Batteries - Wu, Junru; Gao, Ziyao; Wang, Yao; Yang, Xu; Liu, Qi; Zhou, Dong; Wang, Xianshu; Kang, Feiyu; Li, Baohua (Nano-Micro Letters, 2022)
Through tailoring interfacial chemistry, electrolyte engineering is a facile yet effective strategy for high-performance lithium (Li) metal batteries, where the solvation structure is critical for interfacial chemistry. Herein, the effect of electrostatic interaction on regulating an anion-rich solvation is firstly proposed. The moderate electrostatic interaction between anion and solvent promotes anion to enter the solvation sheath, inducing stable solid electrolyte interphase with fast Li+ transport kinetics on the anode. This as-designed electrolyte exhibits excellent compatibility with Li metal anode (a Li deposition/stripping Coulombic efficiency of 99.3%) and high-voltage LiCoO2 cathode. Consequently, the 50 μm-thin Li||high-loading LiCoO2 cells achieve significantly improved cycling performance under stringent conditions of high voltage over 4.5 V, lean electrolyte, and wide temperature range (− 20 to 60 °C). This work inspires a groundbreaking strategy to manipulate the solvation structure through regulating the interactions of solvent and anion for high-performance Li metal batteries. Highlights: 1 The effect of electrostatic interaction on regulating an anion-rich solvation in electrolyte is firstly proposed. 2 The moderate electrostatic interaction between anion and solvent promotes anion-rich solvation sheath, inducing a stable electrolyte|electrode interface with fast Li+ transport kinetics. 3 The outstanding electrochemical performance of 50 μm-thin Li||high-loading LiCoO2 batteries is achieved at high voltage of 4.5 V (even up to 4.6 V), lean electrolyte of 15 μL, and wide temperature range of − 20 to 60 °C.